Modern management of spinal deformities a theoretical, practical, and evidence-based text - Dickson, Robert A. (Thieme, 2018)
Authored by two world-renowned pioneers in the field of spinal surgery, Modern Management of Spinal Deformities: A Theoretical, Practical, and Evidence-Based Text covers the range of spinal deformities-emphasizing scoliosis-and their etiologies, including idiopathic, congenital, neuromuscular, tumors, neurofibromatosis, and more. All too often in other works, too much attention has been focused on how to put in metalwork, without sufficiently discussing the what, when, and why. Authors Dickson and Harms provide a wealth of knowledge through experience that shows how important newer therapeutic.